Adoption of Eco-Friendly Faux Leather: Examining Consumer Attitude With the Value–Belief–Norm Framework. (October 2016) - Kim, HaeJung; Kim, JiYoung; Oh, Kyung Wha; Jung, Hye Jung
Eco-Friendly Faux Leather (EFFL) has recently been developed to minimize harmful environmental impacts; this product also has a low carbon footprint. However, consumers are lagging behind in eco-friendly product adoption due to their value, belief, and attitude gaps. To provide the best available social-psychological account of consumers' adoption of EFFL products, the consumer attitude model was tested as an extension of the Value-Belief-Norm (VBN) framework. Online survey panel data were collected on 602 respondents from U.S. and U.K. Structural Equation Modeling and Multiple Group Analysis were employed to test the hypothesized attitude model. The findings support the conclusion that there is significant causality among environmental value, pro-environmental belief, and the norm of individual responsibility, but no difference regarding the VBN concurrence was found between the two countries. Practical implications and theoretical suggestions for understanding consumer attitude towards a new eco-friendly product are proposed.